Development of a capability and skillset framework for the implementation of resilient nature-based water solutions (RNBWS) in the MENA Region - Parkes, Richard; Fragaszy, Stephen; Belhaj Fraj, Makram; Abdelwahab, Noura; Mandouri, H.; Slehat, F.; Hayajneh, A.; Rabi, A.; Amleh, N.; AbdelMeguid, A.; Maowod, G.; Khatib, B.; et al. (International Water Management Institute, 2025)
The Middle East and North Africa (MENA) Region is one of the most water-scarce in the world, with agriculture accounting for 65% of total water use. This challenge is compounded by land degradation and the intensifying impacts of climate change. In response, the Al Murunah project—meaning “flexibility” in Arabic—was launched to enhance water security through resilient nature-based water solutions (RNBWS) in Egypt, Jordan, Lebanon, and the Occupied Palestinian Territories (OPT).